2009
DOI: 10.1089/ten.tea.2009.0081
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Channel Bridges for Spinal Cord Injury: Cellular Characterization of Host Response

Abstract: Bridges for treatment of the injured spinal cord must stabilize the injury site to prevent secondary damage and create a permissive environment that promotes regeneration. The host response to the bridge is central to creating a permissive environment, as the cell types that respond to the injury have the potential to secrete both stimulatory and inhibitory factors. We investigated multiple channel bridges for spinal cord regeneration and correlated the bridge structure to cell infiltration and axonal elongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 46 publications
4
90
0
Order By: Relevance
“…A second biomaterials approach has sought to direct axonal growth through the damaged region of the spinal cord using 3D structured bridges that incorporate guidance conduits or channels [22-29]. In this regard, we have previously reported the development of porous, multi-channel poly(lactide-co- glycolide) (PLG) bridges in a rat thoracic SCI model [28-31]. In these studies, PLG bridges with linear channels and interconnected pores in vivo showed rapid ingrowth of cells and filled the space normally occupied by a cystic cavity, stabilizing the injury site.…”
Section: Introductionmentioning
confidence: 99%
“…A second biomaterials approach has sought to direct axonal growth through the damaged region of the spinal cord using 3D structured bridges that incorporate guidance conduits or channels [22-29]. In this regard, we have previously reported the development of porous, multi-channel poly(lactide-co- glycolide) (PLG) bridges in a rat thoracic SCI model [28-31]. In these studies, PLG bridges with linear channels and interconnected pores in vivo showed rapid ingrowth of cells and filled the space normally occupied by a cystic cavity, stabilizing the injury site.…”
Section: Introductionmentioning
confidence: 99%
“…These tracts guide nerve sprouting and stimulate the formation of nerve bundles, which may in-turn benefit axonal regeneration [88]. It was discovered that the use of multiple channel bridges in the treatment of SCI can direct the growth of neural fibers and facilitate spinal cord regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have suggested that providing physical support via biomaterials in the acute phase after SCI may prevent cyst formation and reduce glial scar deposition [Prang et al, 2006;Yang et al, 2009b;Tuinstra et al, 2013b;Pawar et al, 2015b]. In the case of hydrogel biomaterials, this support may be provided by the mechanical strength or swelling pressure exerted on the surrounding tissue to hold the implant in position and form a tight interface with the host tissue.…”
Section: Design Considerations For Hydrogels Promoting Sci Repairmentioning
confidence: 99%
“…Biomaterials that provide structural support and contain cell-scale macropores can prevent cyst formation and promote ample cell infiltration within the first few days of implantation, allowing a permissive interface between the biomaterial and the host spinal cord tissue [Yang et al, 2009b;Tuinstra et al, 2012;Thomas et al, 2013]. This early integration results in reduced glial scar deposition, which can allow more regenerating axons to enter, cross and exit the injury site via polymeric bridges [Tuinstra et al, 2012[Tuinstra et al, , 2013aPawar et al, 2015a].…”
Section: Host-biomaterials Interfacementioning
confidence: 99%